Beneficial Roles of 1-MCP on Regulation of Photosynthetic Electron Transport and Energy Dissipation in Chrysanthemum Under Heat Stress - Runtian Miao; Xiaoman Liu; Yilin Zhao; Yanli Zhao; Han Dong; Gan Huang; Yonghua Li (Horticulturae)
1-Methyl cyclopropene (1-MCP) is known as an ethylene antagonist, yet its mechanisms in regulating photosynthetic electron transport and energy dissipation in chrysanthemum under heat stress are not well understood. Here, the chlorophyll a fluorescence and modulated 820 nm reflection transients were analyzed in heat-tolerant and heat-sensitive chrysanthemum plants. This study demonstrates that 1-MCP pre-treatment helps maintain the net photosynthetic rate (Pn) and the reaction center activity of photosystems I and II (PSI and PSII) during heat stress. Specifically, 1-MCP treatment significantly increases the fraction of active oxygen-evolving complex (OEC) centers and reduces relative variable fluorescence intensity at the J step (VJ) as well as the efficiency of electron transfer at the PSI acceptor side (δRo). These effects mitigate damage to the photosynthetic electron transport chain. Additionally, 1-MCP-treated plants exhibit decreased quantum yield of energy dissipation (φDo) and reduced energy flux per reaction center (DIo/RC). Overall, 1-MCP enhances light utilization efficiency and excitation energy dissipation in the PSII antennae, alleviating heat stress-induced damage to PSI and PSII structures and functions. This study not only advances our understanding of 1-MCP’s regulatory role in photosynthetic processes under heat stress but also provides a basis for using exogenous substances to improve chrysanthemum heat resistance.